5p+9=17+4p

Simple and best practice solution for 5p+9=17+4p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p+9=17+4p equation:


Simplifying
5p + 9 = 17 + 4p

Reorder the terms:
9 + 5p = 17 + 4p

Solving
9 + 5p = 17 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
9 + 5p + -4p = 17 + 4p + -4p

Combine like terms: 5p + -4p = 1p
9 + 1p = 17 + 4p + -4p

Combine like terms: 4p + -4p = 0
9 + 1p = 17 + 0
9 + 1p = 17

Add '-9' to each side of the equation.
9 + -9 + 1p = 17 + -9

Combine like terms: 9 + -9 = 0
0 + 1p = 17 + -9
1p = 17 + -9

Combine like terms: 17 + -9 = 8
1p = 8

Divide each side by '1'.
p = 8

Simplifying
p = 8

See similar equations:

| (17x)+(-3x)= | | -3t+6=21 | | x-8.8=-4.3 | | 9x+4x+4+8=8x+3+4x | | 2(16n+3)=-12 | | 10x+5(6)=0 | | (5x)(14x)+7=0 | | m(5-x)=2-y | | 3(x-5)=-12 | | a(c-5)+s(c-5)=0 | | g=3g+3u | | 20a^2-23ab+6b^2=0 | | 5(6z-1)-3(z+3)=11(z+1) | | 9x-(4x-5)-(-6x+1)= | | 22=0 | | 11x-77=0 | | 3x^2-25x+42=0 | | 275m^2+396n^2=0 | | 4y+112=180 | | x^2-x-48=16 | | 0.5(x-0.08)=0 | | x/3=3x-1 | | ln(x)+ln(8x)=-3 | | 5y+20=0 | | 5b+7b=60 | | s^2-12s+36= | | (x-2)/3=8 | | (x-2)/3-5=3 | | 4x^3+12x^2+10x+10=0 | | x-2/3-5=3 | | 2x+30+x= | | 24=-8(0.3p+9) |

Equations solver categories